2007
DOI: 10.1016/j.ejpain.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vanilloid receptor 1 (TRPV1) expression following lingual nerve injury

Abstract: We have investigated a possible role for vanilloid receptor 1 (TRPV1), a transducer of noxious stimuli, in the development of neuropathic pain following injury to a peripheral branch of the trigeminal nerve. In nine adult ferrets the left lingual nerve was sectioned and recovery permitted for 3 days, 3 weeks or 3 months (3 ferrets per group). A retrograde tracer, fluorogold, was injected into the damaged nerve to identify associated cell bodies in the trigeminal ganglion. Three further ferrets, receiving only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
7
31
0
Order By: Relevance
“…In the same sections, TRPV 1 protein was found in approximately 39% of total neurons (659/1682 neurons). Although this proportion is slightly higher than that reported by others (Biggs et al, 2007), it is very similar to results obtained during the initial characterization of this antibody, as well as to previous findings from our lab (Guo et al, 1999;Dussor et al, 2003). Further analysis of the coexpression patterns of these 2 receptors revealed that ~ 64% of TRPV 1 -expressing neurons co-expressed EP2 (426/659 neurons).…”
Section: Resultssupporting
confidence: 91%
“…In the same sections, TRPV 1 protein was found in approximately 39% of total neurons (659/1682 neurons). Although this proportion is slightly higher than that reported by others (Biggs et al, 2007), it is very similar to results obtained during the initial characterization of this antibody, as well as to previous findings from our lab (Guo et al, 1999;Dussor et al, 2003). Further analysis of the coexpression patterns of these 2 receptors revealed that ~ 64% of TRPV 1 -expressing neurons co-expressed EP2 (426/659 neurons).…”
Section: Resultssupporting
confidence: 91%
“…After peripheral nerve injury, TRPV1 expression was observed with different patterns in the injured and uninjured region in the DRG and TG. 3,14 The expression of TRPV1 protein was changed at the injured (fluorogold-positive) and in the associated uninjured (fluorogold-negative) TG neurons after lingual nerve injury. 3 TRPV1 expression was also increased in the spared (uninjured) L4 DRG while reduced in the injured L5 DRG.…”
Section: Differential Expression Of Trpv1 In Uninjured and Injured Nementioning
confidence: 98%
“…10 Studies in the trigeminal system also have shown altered changes in expression of neuropeptides and ion channels in TG following nerve injury. 3,10 One candidate molecule involved in the development of neuropathic pain is TRPV1 channels. Although TRPV1 is thought to function as a noxious heat sensor in the peripheral nerve terminal 5 and is essential for the development of thermal hypersensitivity during inflammation, 9 TRPV1 has been implicated in the development of injury-induced neuropathic pain since changes in its expression have been observed following peripheral nerve injury.…”
mentioning
confidence: 99%
“…Activation of TRPV1, by external stimuli or endogenous agonists like anandamide (AEA), produces inward cation current, which may be involved in the sensitisation of nociceptive DRG neurons that causes hyperalgesia (Jara-Oseguera et al, 2008;Starowicz et al, 2008). Under pathological conditions, TRPV1 expression in nociceptive DRG neurons is altered in various models of peripheral neuropathy (Biggs et al, 2007;Hudson et al, 2001;Kim et al, 2008;Rashid et al, 2003). The association of TRPV1 expression level with pain perception remains unclear, so the importance of channel sensitisation, manifested by the reduced activation threshold was postulated (reviewed in Palazzo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%